Association of maternal depression and infant nutritional status among women living with HIV in Tanzania. Issue 3 (8th November 2014) - Kaaya, Sylvia; Garcia, Maria E.; Li, Nan; Lienert, Jeffrey; Twayigize, William; Spiegelman, Donna; Smith Fawzi, Mary C.
Abstract: Antenatal and post‐natal depression has demonstrated a significant burden in sub‐Saharan Africa, with rates ranging from 10% to 35%. However, perinatal women living with HIV in Tanzania have reported an even greater prevalence of depression (43–45%). The primary goal of this study was to examine the relationship between maternal depression and infant malnutrition among women living with HIV. The design was a retrospective cohort study within the context of a randomised controlled trial among women living with HIV and their infants. Within this trial, 699 mother–child pairs were analysed for the present study. Although antenatal depression was not associated with infant malnutrition and post‐natal depression was negatively associated [relative risk (RR = 0.80, P = 0.04], cumulative depression demonstrated a positive association with infant wasting (RR = 1.08, P < 0.01) and underweight (RR = 1.03, P < 0.01) after controlling for confounding factors. Variation in the association between depression and infant nutritional status was observed for episodic vs. chronic depression. These findings suggest that providing evidence‐based services for persistent depression among women living with HIV may have an effect on infant malnutrition. In addition, other positive outcomes may be related to infant cognitive development as well as HIV disease prognosis and survival among women.